Serum B12, homocysteine, and anti-parietal cell antibody levels in children with autism. (1st March 2022) - Erden, Semih; Akbaş İleri, Betül and Sadıç Çelikkol, Çağla and Nalbant, Kevser and Kılınç, İbrahim and Yazar, Abdullah
Abstract: Aims: To compare vitamin B12, homocysteine, and anti-parietal cell antibody (APCA) levels between children with ASD and controls, paired in terms of age, sex, and socioeconomic level. Methods: The research group consisted of 69 children, 36 with ASD and 33 controls. The severity of ASD was determined using the Childhood Autism Rating Scale (CARS). Serum vitamin B12, homocysteine and human anti-parietal cell levels were analysed using enzyme-linked immunosorbent assay. Results: The serum vitamin B12 and homocysteine levels in children with ASD were lower than in the control group, but there was no significant difference in terms of APCA levels. Conclusions: Deficiencies in micronutrients, such as B12, may play a role in the pathogenesis and clinical symptoms of autism. However, it is believed that these parameters should be analysed in a wider population to clarify their effect on the aetiology of ASD. KEY POINT: We hypothesised that low levels of vitamin B12 and homocysteine levels reported in previous studies might be associated with APCA levels. The homocysteine and B12 levels were found to be significantly lower in children with ASD. There was no significant difference in serum APCA levels. No significant relationship was found between B12 levels and APCA. Given all these findings, it can be stated that vitamin B12 deficiency is not associated with an absorption-related mechanism due to the presence of APCA. Deficiencies in micronutrients, such as B12, may play a role in the pathogenesis and clinical symptoms of autism. In future studies, it will be beneficial to investigate other mechanisms that may cause vitamin B12 deficiency.